Pemberdayaan Ekonomi Kelompok Tani Desa Nyogan Kabupaten Muaro Jambi Melalui Pemanfaatan Lahan Tidak Produktif dengan Penanaman Tanaman Lada Perdu (Piper Nigrum) - Anis Tatik Maryani; Tiur Hermawati; Sri Mulyati (Universitas Serang Raya, 2018)
Pepper Plant (Piper nigrum L), better known as pepper, is one of the most economically valuable plantation commodity crops that has the opportunity to be developed in order to increase economic income for the State and for the farming community. This plant starts to bear fruit at the age of 2-3 years. Historically, the Nyogan villagers used to plant climbing pepper as their livelihood. So far, farmers have planted climbing pepper which requires a sturdy climbing pole. Climbing poles for pepper plants besides being expensive are also increasingly rare nowadays, for the Nyogan villagers to do socialization and planting of pepper shrubs. In theory, shrub pepper plants will grow and develop well if cultivated properly and grow without climbing poles so as to reduce the cost of purchasing climbing poles and do not require large areas. On this basis it is very possible if applied to sleeping land that is not used anymore or (on land that already has unproductive commodities). Pepper plants are very likely to be developed on people's lands around residential areas or empty plantation areas that have not been utilized in the Nyogan Village, Mestong Subdistrict, Muaro Jambi Regency. By utilizing this pattern, people can use their land to be productive and have economic and ecological added value